2015
DOI: 10.1007/s12220-015-9608-4
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity and Infinitesimal Deformability of Ricci Solitons

Abstract: In this paper, an obstruction against the integrability of certain infinitesimal solitonic deformations is given. Using this obstruction, we show that the complex projective spaces of even complex dimension are rigid as Ricci solitons although they have infinitesimal solitonic deformations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…which implies that v h,K is a constant. Then, the operator N in (26), related to the second variation formula, reduces to…”
Section: ∇G : Omentioning
confidence: 99%
See 1 more Smart Citation
“…which implies that v h,K is a constant. Then, the operator N in (26), related to the second variation formula, reduces to…”
Section: ∇G : Omentioning
confidence: 99%
“…Lemma 4.2. Let N be the second variation operator on a steady gradient generalized Ricci soliton (M, g, H, f ) defined in (26). Then,…”
Section: Introductionmentioning
confidence: 99%
“…Munteanu [6] discussed the curvature behavior of four dimensional shrinking gradient Ricci solitons. Kroencke [7] showed that though complex projective spaces of even complex dimension have infinitesimal solitonic deformations, they are rigid as Ricci solitons. Catino et al [8] provided some necessary integrability conditions for the existence of gradient Ricci solitons in conformal Einstein manifolds.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem C (Kröncke, [18]). The Fubini-Study metric on CP 2n is isolated in the moduli space of Ricci solitons.…”
mentioning
confidence: 99%
“…Theorem 5.3 (Kröncke, Theorem 5.7 in [18]). Let (M, g) be an Einstein metric with Einstein constant λ > 0 and let v ∈ V −2λ .…”
mentioning
confidence: 99%